A Case Report of Postmortem Radiography of Acute, Fatal Abdominal Distension After Binge Eating. (December 2016) - Usui, Akihito; Kawasumi, Yusuke; Ishizuka, Yuya; Hosokai, Yoshiyuki; Ikeda, Tomoya; Saito, Haruo; Funayama, Masato
Abstract : Abstract: This case report describes a woman who developed fatal gastric dilatation after binge eating. She called an ambulance because of stomach pain. When she arrived at the hospital, she did not look seriously ill. However, she rapidly became unconscious and collapsed immediately after she was laid on the examination table in a supine position. Postmortem chest x-ray and computed tomography showed right shift of the mediastinum and raised left diaphragm caused by massive gastric distension. Computed tomography showed no visible inferior vena cava. We think that her sudden deterioration was caused by movement of her stomach contents. Radiographic images provided some clues to the cause of her rapid collapse and death.